Analisis Deviasi Rencana Operasi Harian terhadap Realisasi Operasi sebagai Dasar Sistem Peringatan Dini pada PLTGU PT XYZ - Ramadhan, Muhammad Rafi Willy; Sumiati, Sumiati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Discrepancies between the Daily Operation Plan (ROH) and actual operation are issues that can affect the efficiency and operational costs of combined-cycle power plants. This study aims to analyze deviations between ROH and the actual realization of electricity production as well as the consumption of natural gas and High Speed Diesel (HSD) at the PT XYZ Combined Cycle Power Plant. The research was conducted using daily operational data from September to November 2025 obtained from the Planning and Operation Control and Commercial Division. The method applied was deviation analysis by calculating absolute and percentage differences between planned and actual values, which were then classified based on predefined performance thresholds. The results indicate that significant deviations still occurred during several operational periods, particularly in fuel consumption. As a recommendation, a simple spreadsheet-based early warning system using Microsoft Excel was developed to support daily operational monitoring and performance evaluation.